1998
DOI: 10.1046/j.1523-1755.1998.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein as an outcome predictor for maintenance hemodialysis patients

Abstract: The data presented herein suggest that: (1) strong predictable associations exist among laboratory proxies for malnutrition, anemia, and the acute phase reaction, and (2) the pathobiology implied by these laboratory abnormalities influence patients' mortal risk primarily through depletion of vital body proteins, not inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
214
6
11

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(248 citation statements)
references
References 38 publications
17
214
6
11
Order By: Relevance
“…The association between these markers and mortality has been recognized for over a decade and this has been confirmed. [27][28][29] In this multivariate analysis, TA albumin was not associated with mortality for PD patients. Our data showed that the TA albumin decreased as the grade of the Davies index increased.…”
Section: Discussionmentioning
confidence: 59%
“…The association between these markers and mortality has been recognized for over a decade and this has been confirmed. [27][28][29] In this multivariate analysis, TA albumin was not associated with mortality for PD patients. Our data showed that the TA albumin decreased as the grade of the Davies index increased.…”
Section: Discussionmentioning
confidence: 59%
“…In the past decade, much attention has been focused on CRP as a prototypical marker of inflammation, and elevated levels of CRP are associated with mortality and cardiovascular disease in the CKD population (21,36,38). The lack of association that was seen in our study potentially may be explained by the following observations.…”
Section: Discussionmentioning
confidence: 65%
“…Serum albumin is one of the key indicators of dialysis quality (34). Hypoalbuminemia has been demonstrated to be a strong predictor of death (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies relied on assumptions about the role of inflammation in the modification of nutritional status of chronic hemodialysis patients based on cross-sectional findings (1,17,18,39Ϫ41), but not all them were able to provide clinical evidence supporting this link between PEW and nutritional markers in HD patients (40,41). A few studies have attempted to follow HD patients longitudinally to determine whether nutritional status is associated with inflammation over time.…”
Section: Discussionmentioning
confidence: 99%